2016
DOI: 10.22490/21456453.1554
|View full text |Cite
|
Sign up to set email alerts
|

Eliminación de partículas similares a Cryptosporidium ooquistes por filtración directa ascendente utilizando un coagulante natural: estudio a escala piloto

Abstract: <p><em>En la presente investigación fueron realizados experimentos de filtración de flujo ascendente en  línea, a escala piloto, para evaluar el desempeño del coagulante natural quitosano en la extracción de microesferas de poliestireno con dimensiones similares a Cryptosporidium oocysts, en el tratamiento de aguas con turbidez natural aproximada de 30 uT, inducida con caolinita. Los parámetros evaluados fueron turbidez, materia orgánica (absorbancia a 254 nm) y concentración de microesferas. Inici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Regarding upflow filtration, Méndez et al [18], using chitosan as a coagulant, reported a microsphere removal efficiency of 4.66 log, on average, therefore higher than that obtained in this work. Nascimento et al [17] obtained Cryptosporidium oocyst removal efficiencies ranging from 2.80 to 4.20 log.…”
Section: Fluorescent Microspherescontrasting
confidence: 75%
See 2 more Smart Citations
“…Regarding upflow filtration, Méndez et al [18], using chitosan as a coagulant, reported a microsphere removal efficiency of 4.66 log, on average, therefore higher than that obtained in this work. Nascimento et al [17] obtained Cryptosporidium oocyst removal efficiencies ranging from 2.80 to 4.20 log.…”
Section: Fluorescent Microspherescontrasting
confidence: 75%
“…Nascimento et al [17] obtained Cryptosporidium oocyst removal efficiencies ranging from 2.80 to 4.20 log. These two authors [17,18] operated an upflow pilot-scale filter with a similar configuration to the one used in the present work.…”
Section: Fluorescent Microspheresmentioning
confidence: 99%
See 1 more Smart Citation